A Secure Transmission of Medical Images by Single Label SWT and SVD based Non-Blind Watermarking Technique - Pathak, Yatindra; Jain, Yogendra Kumar; Dehariya, Satish (INFOCOMP Journal of Computer Science, 2015)
Healthcare plays a most important part in human life today. Due to high quality of health-care, several dangerous diseases became curable now. But a major concerned problem with high quality healthcare is that it is not equally accessible throughout the world. The part of the problem is that the recipient and also the provider must be physically present within the same place. To overcome this problem information and communication technology has been used as a way by which healthcare can be delivered throughout the world. With the help of internet, medical professionals can be share medical reports and taking advice of experts before diagnosed that person. But use of internet also creates some issues such as security and safety of the medical data and protects their confidentiality, integrity and authenticity. Digital watermarking can be used as an important tool for the security and copyright protection of medical images. A new scheme for non-blind image watermarking is offered in this article that is robust against affine transformation and ordinary image manipulation. The suggested watermarking scheme based on Singular Value Decomposition(SVD) and Stationary Wavelet Transform(SWT). Once SWT is applied to both watermark and cover images, SVD is applied to the lower frequency LL subbands of both images. Now alter singular matrix (a diagonal matrix which contains singular values of image as its diagonal elements) of the cover image using singular matrix of the visual watermark. The proposed technique is robust against nearly all common attacks. Study and experimental results illustrate higher performance of the proposed method in comparison with the DWT method.